Whole‐slide laser microdissection for tumour enrichment. Issue 2 (9th December 2020) - Coope, Robin JN; Schlosser, Colin; Corbett, Richard D; Pleasance, Stephen; Tessier‐Cloutier, Basile; Pandoh, Pawan; Kirk, Heather; Haile, Simon; Zhao, Yongjun; Mungall, Andrew J; Marra, Marco A
Abstract: The practical application of genome‐scale technologies to precision oncology research requires flexible tissue processing strategies that can be used to differentially select both tumour and normal cell populations from formalin‐fixed, paraffin‐embedded tissues. As tumour sequencing scales towards clinical implementation, practical difficulties in scheduling and obtaining fresh tissue biopsies at scale, including blood samples as surrogates for matched 'normal' DNA, have focused attention on the use of formalin‐preserved clinical samples collected routinely for diagnostic purposes. In practice, such samples often contain both tumour and normal cells which, if correctly partitioned, could be used to profile both tumour and normal genomes, thus identifying somatic alterations. Here we report a semi‐automated method for laser microdissecting entire slide‐mounted tissue sections to enrich for cells of interest with sufficient yield for whole genome and transcriptome sequencing. Using this method, we demonstrated enrichment of tumour material from mixed tumour–normal samples by up to 67%. Leveraging new methods that allow for the extraction of high‐quality nucleic acids from small amounts of formalin‐fixed tissues, we further showed that the method was successful in yielding sequence data of sufficient quality for use in BC Cancer's Personalized OncoGenomics (POG) program. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.